2019
DOI: 10.21203/rs.2.16882/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tobacco and electronic cigarette cues for smoking and vaping: an online experimental study

Abstract: Objective This study examined whether exposure to smoking and vaping cues the urge to smoke or vape. It extends previous studies on first-generation cigalikes (visually similar to cigarettes) and second-generation devices (visually similar to pens) by including third-generation tank system devices (larger bulky units). In an online experiment, participants were randomly assigned to view one of four videos, which included smoking, vaping (cigalike or tank system), or neutral cues. The primary outcome was urge t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…A previous field trial of a different intervention (glass shape) in 24 venues with a similar design to the current study found a mean difference of -35 litres in the volume of draught alcoholic beer sold between intervention and control periods (A-B) (21). The standard deviation (SD) of this mean difference was 141 litres.…”
Section: Sample Size Calculationsupporting
confidence: 61%
See 1 more Smart Citation
“…A previous field trial of a different intervention (glass shape) in 24 venues with a similar design to the current study found a mean difference of -35 litres in the volume of draught alcoholic beer sold between intervention and control periods (A-B) (21). The standard deviation (SD) of this mean difference was 141 litres.…”
Section: Sample Size Calculationsupporting
confidence: 61%
“…Venues were contacted either by directly contacting owners and managers of bars and public houses that had taken part in at least one of our previous field studies (21,22), or from a list of bars and public houses collected on Google Maps. Venues were contacted via phone and email.…”
Section: Recruitmentmentioning
confidence: 99%